Entrepreneurship education at Indian industrial training institutes: A case study of the prescribed, adopted and enacted curriculum in and around Bangalore - Lea Zenner; Kumar Kothandaraman; Matthias Pilz (International Journal for Research in Vocational Education and Training (IJRVET), 2017)
On the one hand, India is a growing economy that needs skilled labour, self-employed entrepreneurs and employees to tackle its economic and social challenges. On the other hand, India faces high unemployment rates, especially among young people. Graduates from industrial training institutes (ITIs) in particular are often facing difficulties in pursuing self-employment. Entrepreneurship education is an essential element in preparing young people for self-employment. This paper analyses how and to what extent entrepreneurship education has been conceived and implemented in vocational schools in and around Bangalore to face these challenges. Methodologically the authors use a three-step approach following the theories of a `prescribed', `adopted' or `enacted' curriculum. Qualitative interviews are used for the analysis of the adopted and enacted curriculum. The authors conclude that whereas the prescribed curriculum includes several elements of entrepreneurship education and teacher's understanding is in line with the prescription, the understanding is seldom translated into input in the day-to-day teaching. The plausible reasons for this gap are discussed in this paper.
Keywords: 330; VET; Vocational Education and Training; Entrepreneurship Education; India; Prescribed Curriculum; Enacted Curriculum; Industrial Training Centers; Industrial Training Institutes